Pemberian Perasan Buah Mengkudu (Morinda citrifolia) untuk Pengendalian Argulus Pada Ikan Mas Komet (Carassius auratus auratus) [Giving Morinda Fruit Distilation (Morinda citrifolia) For Argulus Handling On Carrasius auratus auratus] - Kismiyati Kismiyati; Iqbal Ghazali; Gunanti Mahasri (Faculty of Fisheries and Marine Universitas Airlangga, 2012)
Abstract This study aims to determine the effect of giving Morinda fruit distilation for handling Argulus on Carrasius auratus auratus. The research method that used was experimentally with Completely Randomized Design (CRD) with five treatments and four replications. The used treatment are : medium with Morinda distilation mixed 0% (A), medium with Morinda distilation mixed 2,5% (B), medium with Morinda distilation mixed 3% (C), medium with Morinda distilation mixed 3,5% (D), medium with Morinda distilation mixed 4% (E). The results showed that giving Morinda fruit distillation on Carrasius auratus auratus which have Argulus infest significantly different (p <0.05) with the best treatment in D with six releasing Argulus and that fish can survive within 15 minutes dipping. The lowest treatment result in A (control) with nothing releasing Argulus. Water quality parameters are supporting this research. Supporting parameters measured during the study is the water temperature ranges 27° C, pH 7,5-8,5, DO 8 mg/L to 5 mg/L, and salinity from 0 to 3 ppt. Water quality parameter are still within tolerance limit for Carrasius auratus auratus